-3(2x+7)=
-4(a-b)=
7(5-c)=
-12(-⅓+z)=
a(a-b)=
2a(3a-2)=
-x(5y+x)=
-2x(-2x-3+y)=
(2x+6):2=
(3x-12):3=
(4x-8):(-2)=
(10x+15):5=



3a²92a-b)-b(a³-ab-1)-2ab(-1,5a+3)=
a(b-c)+b(c-a)+c(a-b)=
-4a²b(b-a/2)+2ab(2ab-a)=




15ab-6b=
4xyz+10xz=
8k²l³-4k²l=
5m³n+20m²n²=
9a²b³-6a³b+2a²b²=
2,1x³+0,7x³y-1,4x²=



Odpowiedź :

-3(2x+7)= -6x - 21
-4(a-b)= -4a + 4b
7(5-c)= 35 - 7c
-12(-⅓+z)= 4 -12z
a(a-b)= a² -ab
2a(3a-2)= 6a² - 4a
-x(5y+x)= - 5xy - x²
-2x(-2x-3+y)= 4x² + 6x - 2xy
(2x+6):2= x + 3
(3x-12):3= x - 4
(4x-8):(-2)= -2x + 4
(10x+15):5= 2x +3

-3(2x+7)= -6x-21
-4(a-b)= -4a+4b
7(5-c)= 35-7c
-12(-⅓+z)= 4-12z
a(a-b)= a²-ab
2a(3a-2)= 6a²-4a
-x(5y+x)= - 5xy-x²
-2x(-2x-3+y)= 4x²+6x-2xy
(2x+6):2= x+3
(3x-12):3= x-4
(4x-8):(-2)= -2x+4
(10x+15):5= 2x+3


a(b-c)+b(c-a)+c(a-b)=b-c+bc-ab+ac-bc=b-c-ab+ac

-4a²b(b-a/2)+2ab(2ab-a)=
(3a²92a-b)-b(a³-ab-1)-2ab(-1,5a+3)=

Przykro mi tych dwóch nie potrafie. ;/


15ab-6b= 3b(5a-2)
4xyz+10xz= 2xz(2y+5)
8k²l³-4k²l= 2k²l(4l²-2)
5m³n+20m²n²= 5m²n(m+4n)
9a²b³-6a³b+2a²b²= a²b(9b²-6a+2b)
2,1x³+0,7x³y-1,4x²= 0,7x²(3x+xy-2)